PENGARUH KARAKTERISTIK PEKERJAAN DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN PT. INTI (PERSERO) BANDUNG - Rifa Rahmadiah, - (2020)
The success of an organization can be seen by measuring how effective the organization is in achieving its established strategic goals, through empowering employees in the company. Employees are required to commit to their work in order to support the company's objectives, as done by PT. INTI (Persero) Bandung. This condition makes PT. INTI (Persero) Bandung implements strategies to improve their job characteristic condition and the effectiveness of transformational leadership styles in an effort to increase the organizational commitment of their employee. This research aims to obtain (1) an overview job characteristics, (2) an overview of transformational leadership styles. (3) an overview of the organizational commitment, (4) the influence of job characteristics on organizational commitment, (5) the influence of transformational leadership styles on organizational commitment. The method used in this study is mixed methods research using sampling techniques "probability sampling" of 68 respondents through the spread of polls. The data analysis technique used is a multiple linear regression with computer software tool Statistical Product for Service Solutions (SPPS) 25.0 for windows. The findings in this study show that (1) an overview of job characteristics is in the good category with a score of 2,819 or 82.9%, (2) an overview of transformational leadership styles is in the effective category with a score of 3,724 or 78.2%, (3) an overview of the organizational commitment is in high categories with a score of 2,467 or 80.6%, (4) job characteristics affecting organizational commitment by 30.8%, (5) transformational leadership style affecting organizational commitment by 9.7%. Based on the results of this study, it is recommended that improvements in the conditions of job characteristics can be carried out through regular administration of performance reports, compiling informative and easy-to-understand performance reports, and rewarding employee as a sign of good performance. As for transformational leadership style, it is recommended to develop the idea of each employee in work, through training and routine of employees in day-to-day work, and to involve more employees in decision making, this effort is expected to support the increased of organizational commitment. The low level of organizational commitment to the employee causes company's productivity and performance not maximal.